Tuberculosis and/or HIV Infection and Associated Socio-Behavioural Factors in Immigrants, in Portugal: A Cross-Sectional, Community-Based Descriptive Study - Rhaisa Farias; Isabel Couto; Marta Pingarilho; Inês Fronteira (Karger Publishers, 2022)
Introduction: Portugal is one of the countries in Western Europe with the highest prevalence of tuberculosis (TB) and human immunodeficiency virus (HIV). The prevalence among migrants is estimated to be higher than among non-migrants, which suggests a greater vulnerability of this population. Aim: To describe the distribution of TB, HIV and HIV-TB co-infection and socio-behavioural factors associated with immigrants that lived in the metropolitan area of Lisbon and used the services of a Non-Governmental Organization (NGO). Methods: Quantitative, cross-sectional and descriptive pilot study. An anonymous and structured questionnaire developed specifically for the study was applied by NGO employees duly trained for this purpose to a purposeful sample of 100 immigrants attending health services in an NGO in the metropolitan area of Lisbon, Portugal. Results: The prevalence of HIV-TB extrapulmonary coinfection and HIV infection was 1% (n = 1) and 17% (n = 17), respectively. Only 1 immigrant had 4 out of the 5 symptoms suggestive of TB. No cases of pulmonary TB were identified, although 3 of the immigrants reported having been treated for pulmonary TB in the past. The participants were young, mainly female and some were male-to-female transsexuals. Most were from the community of Portuguese-speaking countries, especially from Brazil, and almost half of them had not regularized their immigration status. Additionally, almost one-fifth of immigrants were unemployed (17%), and one-sixth performed sex work (14%). Most of the participants (71%) sometimes used or never used a condom during sexual intercourse. Additionally, 40% revealed using illicit drugs and 1% said that they had shared injection material in the last 12 months. Discussion: Being non-employed, with a low income and a lower level of education, consumption of illicit drugs and regular tobacco consumption were common characteristics in the immigrants studied, which points out social and economic disadvantages that could influence the risk of acquiring HIV and TB. Policies on latent TB infection and TB diagnosis are urgently needed, mainly aimed at vulnerable groups and culturally diverse populations.